Use of Operational Training Simulation in the Study of Ethanol Operating Conditions: A Powerful Tool for Education and Research Performance Improvement (2020)
Currently, virtual education has reached a significant boom in higher education institutions. The latter, considering health emergency due to coronavirus pandemic, which makes it difficult to re-open physical infrastructures. As a consequence of the above, there is concern about experimental development taught by higher education and research institutions, since the execution of the experimental component is still considered a challenge due to uncertainly of on-going infections. Currently, the University of Bremen, Germany has implemented an operational training simulator for the study of bioprocess based on mathematical equations and experimental confirmations. The software enables teaching of virtual handling and operation of bioreactors. Students and engineers can deal with real situations that arise in the plant operation. Fermentations in different modes to reflect its effects on productivity could be studied. The main purpose of this research is determining the best operating conditions for the ethanol continuous production using the BioProcess Trainer software. One of the most important findings suggest a bioreactor feed rate of 5 mL/min charged with 20 g/L of glucose to reach a productivity of 0.037 g/L.h. Results found here demonstrates the Bioprocess Trainer potential capacity not only in the study of industrial plant operating conditions but also regarding educational institutions since mentioned tool improves engineers’ expertise.